Analisis Perbandingan Kinerja Keuangan Bank BNI Tbk Dan Bank Mega Tbk - Nurhasanah Nurhasanah; Aris Munandar; Alwi Alwi (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to analyze the comparative financial performance of Bank Negara Indonesia (BNI) Tbk and Bank Mega Tbk during the period 2018–2022. Financial performance was measured using the ratios of Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The study employed a comparative quantitative method using secondary data obtained from the official websites of both banks and the Indonesia Stock Exchange. The analysis was conducted through descriptive comparison, trend visualization of financial ratios, and independent sample t-test to determine the significance of performance differences. The results indicate that BNI exhibited higher profitability under normal conditions but experienced a significant decline during the COVID-19 pandemic, whereas Bank Mega demonstrated more consistent performance stability throughout the period. These differences in performance are influenced by risk management strategies, operational efficiency, and the respective scales of the banks. The findings have important implications for investors, customers, bank management, and regulators in making decisions regarding investment, risk management, and banking industry supervision.